The structural equation model of factors affecting digital citizenship in Thailand's digital society - Khanchai, Khajonsak; Panyakanphon, Chanaphorn; Puisuwan, Pattaraporn (Journal of Management Science Nakhon Pathom Rajabhat University, 2025)
This research aimed to 1) develop a linear structural equation model of factors affecting digital citizenship in a digital Thai society and 2) examine structural equation model of factors affecting digital citizenship in a digital Thai society using an assessment as a tool to collect data from 720 undergraduate students. The statistics used for data analysis were descriptive statistics and and structural model analysis using Structural Equation Modeling. The results revealed that 1) the proposed structural model demonstrated a good fit with the empirical data (chi-square = 1,025.47, df = 365, p-value = .000, χ²/df = 2.81, NFI = .92, IFI = .94, CFI = .93, RMSEA = .065), and 2) digital competence, digital intelligence, and media profession were significant causal factors influencing digital citizenship at the .01 level. These three variables collectively accounted for 72.1% of the variance in digital citizenship. Additionally, the path analysis indicated that digital competence had the highest direct effect on digital citizenship, followed by digital intelligence and media profession. And no statistically significant indirect effects were observed in the model. These findings underscore the importance of enhancing users’ digital skills and attributes in fostering responsible and engaged digital citizenship within Thai digital society. Article history: Received 5 August 2024 Revised 3 May 2025 Accepted 5 May 2025 SIMILARITY INDEX = 16.71 %